PENGARUH ROA, ROE, EPS DAN NPM TERHADAP HARGA SAHAM INDEKS LQ45 TAHUN 2018-2022 - Sutriyadi, Riko (POLITEKNIK LP3I JAKARTA, 2023)
The capital market in Indonesia has a big role for the country's economy, with the capital market (capital market). Investors as parties who have excess funds can invest their funds in various securities in the hope of obtaining returns. Accurate stock valuation can minimize risk considering stock investment in the capital market is a high-risk type of investment. The share price can change at any time depending on the amount of supply and demand by investors for these shares. Factors that can affect the ups and downs of a company's stock price are internal factors and external factors of the company. This study uses the company's internal factors which are reflected in the company's financial statements. The company's internal factors used are financial ratios such as profitability ratios proxied by Return on Assets (ROA) and Net Profit Margin (NPM), Return on Equity (ROE) and market ratios proxied by Earning Per Share (EPS). This study shows that Return on Assets (ROA) and Return on Equity (ROE) partially have no significant effect on stock prices in the LQ45 Index and Earnings per Share (EPS) and Net Profit Margin (NPM) partially have an effect on significant effect on stock prices on the LQ45 index and ROA, ROE, EPS and NPM simultaneously have an effect on stock prices on the LQ45 index marked by an influence of 45.6%.Keywords: ROA, ROE, EPS, NPM